Communication Policy In System Implementation Personnel Management Information (Simpeg) Bandung City - Susniwati Susniwati; Istikomah Istikomah (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
In order to carry out file transfer and environmental development initiatives, it is necessary to establish a database system within the city of Bandung. Another example is the case that was resolved by both the Personnel Agency and Bandung City Human Resource Development (BKPSDM) through the Personnel Management Information Framework (SIMPEG). The same objective of this study is to evaluate the need for interaction in the context of the Bandung Information Management System (Simpeg).The research above uses quantitative research methods with descriptive approaches such as data collection, analysis, and documentary evidence.The results of the study found policiescommunication on the implementation of the Personnel Management Information System policy at the Bandung City Personnel and Human Resources Development Agency based on the information that has been provided, clear goals and consistency have been implemented properly, this encourages the creation of good policy implementation in government agencies.